HUBUNGAN ANTARA KONTROL DIRI DENGAN KONFLIK BERPACARAN PADA MAHASISWA UNIVERSITAS BINA DARMA PALEMBANG - Sujarwo, Sawi (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2016)
This research determines the relationship  between self control and conflict dating to students majored in computer science of Faculty of Informatics Systems Force 2009 at Bina Darma University Palembang. Hypothesis is the  relationship  between self control and conflict dating to students majored in computer science of Faculty of Informatics Systems Force 2009 at Bina Darma University Palembang. Populations this study were students majored in computer science of faculty of informatics systems force 2009 Bina Darma University Palembang. By taking 118 samples of people. The subject of this research was taken by using Purposive Sampling techniques. Data analysis in this research was sample regression analysis. The results of this study showed there was significant between self control and conflict dating to students majored in computer science of Faculty of Informatics Systems Force 2009 at Bina Darma University Palembang. Contribution were made by self control and dating conflicts was 51% (R square = 0.510). It means 49% were influenced by other factors but they were researched further in this study